Perbedaan Asupan Energi, Protein, Zink, dan Prestasi Belajar pada Anak Stunting dan Non-Stunting Usia Sekolah Dasar di Kecamatan Soko Kabupaten Tuban - Intan Nur Ayuni; Sri Sumarmi (Universitas Airlangga, 2023)
Background: Stunting is identified as a chronic nutritional problem in Indonesia due to a lack of nutritional intake, which has implications for children's cognitive conditions. Stunting can affect achievement and learning abilities, impacting children's learning achievements at school. Objectives: To analyze differences in intake of energy, protein, zinc, and learning achievement in stunted and non-stunted children of primary school age in Soko District, Tuban. Methods: This research was an analytic observational type with a cross-sectional design. A sample of 70 children with stunted nutritional status and 70 non-stunted children from 6 elementary schools in Soko District, Tuban, were taken randomly using a simple random sampling technique. Data were collected through anthropometric measurements, interviews with SQ-FFQ, and report cards for Mathematics and Indonesian. Data analysis used SPSS with independent sample t-test. Results: There were differences in energy intake (p-value = 0.006), protein (p-value = 0.001), zinc (p-value = 0.001), learning achievement in Mathematics (p-value = 0.000) and Indonesian (p-value = 0.008) between stunting and non-stunting student groups in Soko District, Tuban. Conclusions: The intake of energy and protein in the stunting group was mainly in the moderate deficit category, while zinc was in the less category. The intake of energy, protein and zinc in most non-stunting groups was in the sufficient category. Learning achievement for Mathematics and Indonesian subjects in the stunting group was mainly in the moderate category, while the non-stunting group was mostly in the adequate category. Overall, the two groups had differences in energy, protein, zinc intake, and learning achievement.